Teachers’ Beliefs and Practices in Professional Development: A Higher Education Context - Purwanti, Eko (Universitas Ahmad Dahlan, 2024)
This research aims to find out teachers’ beliefs about Teacher Professional Development (TPD) in higher education contexts. Teachers in higher education are primarily responsible for reforming, developing, and distributing science, technology, and art through education, research, and community service. These tasks called Three Pillars of Higher Education or Tri Dharma Perguruan Tinggi are obligatory for all Indonesian teachers. In order to accomplish these three pillars of higher education, teachers should be professional, and in so doing, teachers should have four competencies, comprising professional, pedagogical, social, and personal competence. To accomplish these three pillars of higher education and have these four competencies, teachers must conduct professional development activities. TPD is important to increase the quality of education in higher education around the world. Therefore, teachers are encouraged to conduct TPD regularly and continuously amidst their never-ending works. This phenomenon is experienced by teachers in UMY; hence, it is interesting to investigate teachers’ belief about their TPD activities. This study employed a qualitative approach, particularly a descriptive qualitative research design in which the data were collected from three teachers of an Islamic private university in Yogyakarta. The findings of the study revealed the participants’ beliefs about their TPD, the activities they did in maintaining their TPD, their challenges in implementing TPD, and their strategies in overcoming the problems. In the long term, this research aims to build a culture of professionalism among teachers in higher education, especially in this Islamic private university.